Klasifikasi Tingkat Pemahaman Siswa Kelas VI Sekolah Dasar terhadap Perangkat Keras Komputer Menggunakan Metode Decision Tree - Suchi Azzahro Syarif; Vilianty Rafida; Rizky Zakariyya Rasyad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The development of information technology in education requires students to have a basic understanding of computer hardware from an early age. However, the level of students’ understanding of computer hardware still varies, especially at the elementary school level. This condition can affect students’ ability to understand the use of technology more effectively in computer-based learning processes. This study aims to classify the level of understanding of sixth grade elementary school students regarding computer hardware using the Decision Tree method. The research data were obtained through a questionnaire consisting of 25 questions related to computer hardware. Each student’s answer was assigned points based on its correctness level, then the total score was calculated and converted into a 0–100 scale before being categorized into three classes, namely High Understanding, Moderate Understanding, and Low Understanding based on score ranges adjusted to the distribution of the research data. The data show that there are 30 students in the High Understanding category, 18 students in the Moderate Understanding category, and 6 students in the Low Understanding category. The classification process was carried out using the Decision Tree method with 80% training data and 20% testing data. The model achieved an accuracy of 45% on the test data. The result indicates that the model is not yet optimal in performing balanced classification across all categories of student understanding. The findings of this study contribute to the application of the Decision Tree classification method in elementary education, particularly in identifying students’ understanding of computer hardware based on questionnaire data.